Effect of exposure to ionizing radiation on competitive proliferation and differentiation of hESC. (4th May 2023) - Panyutin, Irina V.; Wakim, Paul G.; Maass-Moreno, Roberto; Pritchard, William F.; Neumann, Ronald D.; Panyutin, Igor G.
Abstract: Purpose: We studied the effects of computed tomography (CT) scan irradiation on proliferation and differentiation of human embryonic stem cells (hESCs). It was reported that hESC is extremely radiosensitive; exposure of hESC in cultures to 1 Gy of ionizing radiation (IR) results in massive apoptosis of the damaged cells and, thus, they are eliminated from the cultures. However, after recovery the surviving cells proliferate and differentiate normally. We hypothesized that IR-exposed hESC may still have growth rate disadvantage when they proliferate or differentiate in the presence of non-irradiated hESC, as has been shown for mouse hematopoietic stem cells in vivo. Materials and methods: To study such competitive proliferation and differentiation, we obtained cells of H9 hESC line that stably express green fluorescent protein (H9GFP). Irradiated with 50 mGy or 500 mGy H9GFP and non-irradiated H9 cells (or vice versa) were mixed and allowed to grow under pluripotency maintaining conditions or under conditions of directed differentiation into neuronal lineage for several passages. The ratio of H9GFP to H9 cells was measured after every passage or approximately every week. Results: We observed competition of H9 and H9GFP cells; we found that the ratio of H9GFP to H9 cells increased with time in both proliferation and differentiation conditions regardless of irradiation, i.e. the H9GFP cells in general grew faster than H9 cells in the mixtures. However, we did not observe any consistent changes in the relative growth rate of irradiated versus non-irradiated hESC. Conclusions: We conclude that population of pluripotent hESC is very resilient; while damaged cells are eliminated from colonies, the surviving cells retain their pluripotency, ability to differentiate, and compete with non-irradiated isogenic cells. These findings are consistent with the results of our previous studies, and with the concept that early in pregnancy omnipotent cells injured by IR can be replaced by non-damaged cells with no impact on embryo development.